Generational policy - Kotlikoff, Laurence J. (Cairoli lecture series., 2003)
How generational policy affects the sustainability of a government's fiscal policy. In these eight 2002 Cairoli Lectures, presented at the Universidad Torcuato di Tella in Buenos Aires, Argentina, Laurence Kotlikoff shows how generational policy works, how it is measured, and how much it matters. Kotlikoff discusses the incidence and measurement of generational policy, the relationship of generational policy to monetary policy, and the vacuity of deficits, taxes, and transfer payments as economic measures of fiscal policy. Kotlikoff also illustrates generational policy's general equilibrium effects with a dynamic life-cycle simulation model and reviews the empirical evidence testing intergenerational altruism and risk sharing. The lectures were delivered as Argentina faced a devastating depression triggered, in large part, by unsustainable generational policy. Throughout the book, Kotlikoff connects his messages about generational policy to the Argentine situation and the Argentine government's policy mistakes.